Optimization of the Extraction Process of Highland Barley β-glucan by Three-phase Partitioning and Its Molecular Weight Distribution - Yang CHEN; Peng WANG; Kaijin PAN; Zhe WANG; Jian XU; Junqiang ZHOU; Ziwei LIAO (Shipin gongye ke-ji, 2023)
Ultrasonic combined with enzymatic pretreatment-assisted three-phase partitioning (UCWEPATPP) was utilized to simultaneously extract the β-glucan, protein and oil from highland barley (Hordeum vulgare L.var.nudum Hook.f.). Based on the single-factor experiments, the extraction process conditions of UCWEPATPP were optimized by response surface methodology (RSM) with the extraction rate of highland barley β-glucan as the index. Scanning electron microscope (SEM) was used to observe the change of surface structure during the extraction of highland barley, and the extraction mechanism of UCWEPATPP was preliminarily analyzed. Finally, the molecular weight range of the obtained highland barley β-glucan was determined using a high performance gel size exclusion chromatography. The results showed that the optimal UCWEPATPP process conditions were as follows: Enzyme addition was 1.0%, ultrasonic time was 9 min, ultrasonic power was 140 W, ammonium sulfate addition was 0.5 g/mL, three-phase extraction temperature was 35 ℃, three-phase extraction time was 1.5 h, the liquid ratio was 1:14 g/mL, the volume ratio of tert-butanol to aqueous phase was 1.3:1, the enzymatic hydrolysis time was 2.0 h. Under the optimal conditions, the extraction rate of highland barley β-glucan was 66.96%±0.05%, the extraction rate of highland barley oil was 81.42%±0.15%, and the extraction rate of highland barley protein was 50.31%±0.23%. Scanning electron microscope results showed that UCWEPATPP made the surface tissue structure of highland barley become transparent and porous. UCWEPATPP not only could extract highland barley β-glucan, protein and oil at the same time, but also could reduce the production cost and improve the utilization of highland barley resources. The actual value of the extraction process and the predicted value had a high degree of fit, which was used to predict the extraction of highland barley β-glucan. In addition, the obtained highland barley β-glucan had a relatively concentrated molecular weight distribution (1.7×105~3.0×105 Da).